South Asian Partition Fiction in English From Khushwant Singh to Amitav Ghosh - Rituparna, Roy (IIAS Publications Series, 2010)
South Asian Partition Fiction in English: From Khushwant Singh to Amitav Ghosh explores a significant cross-section of South Asian fiction in English written on the theme of Partition from the mid-1950s to the late 1980s, and shows how the Partition novel in English traverses a very interesting trajectory during this period - from just 'reporting' the cataclysmic event to theorizing about it. The six novels selected for study (Train to Pakistan, A Bend in the Ganges, Ice-Candy-Man, Clear Light of Day, Midnight's Children, and The Shadow Lines) show that, essentially, three factors shape the contours and determine the thrust of the narratives - the time in which the novelists are writing; the value they attach to women as subjects of this traumatic history; and the way they perceive the concept of the nation. "By a fresh reading of six novels that are representative of the various perspectives on the Partition of the subcontinent, and placing them in a larger historical and literary context, dr. Roy's book fills an important lacuna in current criticism, and does it convincingly." - Peter Liebregts, Professor of Modern Literatures in English, Leiden University "In this thoughtful and thoroughly readable book, Rituparna Roy looks at fictional representations of the cataclysmic birth-pangs of India, Pakistan and Bangladesh, and indicates how literary envisionings mesh in with reportage, historiography, nationhood, femininity and personal identity." - Subir Dhar, Professor of English Literature, Rabindra Bharati University (RBU), Kolkata